Botulism by Clostridium botulinum type C in goats associated with osteophagia - Riet-Correa, Franklin; Medeiros, Rosane M. T.; Tokarnia, Carlos H.; de Carvalho, Ciro J. S.; Franklin, Fabio L. A. A.; Dias, Alexandre C. S.; Ferreira, Rosa M. M. [UNESP]; Silva, Silvana. M. M. S. (Elsevier B.V., 2012)
An outbreak of botulism was detected in goats in the semiarid region of Brazil. In a flock of 460 goats, 38 does were affected and 37 died. Kids and younger goats were not affected. The main clinical signs were flaccid tetraparesis leading to tetraplegia that was often accompanied by twisted neck, tongue paralysis, and muscle tremors. At the time of the visit, 4 out of 11 affected goats were recumbent. Ambulatory goats had uncoordinated and swaying gaits with hypometria and weakness, mainly of the hind limbs. Two recumbent and four ambulatory goats showed twisted neck. Two recumbent goats were euthanized and necropsied. Non-significant gross and histologic lesions were observed. Samples of the liver, gut and rumen content were collected from the two goats and examined for botulinum toxins using the mouse serum neutralization test. The three samples from one goat were positive for type C toxin. Marked osteophagia was observed when the goats had access to bones in the pasture, and the farmer mentioned that osteophagia was common among goats of the flock. A sample of the plant Hybantus ipecaconha, the most abundant forage available for the goats, contained 2800 mg/kg of Ca and 450 mg/kg of P. One soil sample contained 58.12 mg/kg of Ca and 2.02 mg/kg of P. It was concluded that in this outbreak, botulism was associated with osteophagia probably due to phosphorus deficiency. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Botulism; Clostridium botulinum; Flaccid paralysis; Goats; Osteophagia